Optimal timing for initiation of highly active antiretroviral therapy in treatment‐naïve human immunodeficiency virus‐1‐infected individuals presenting with AIDS‐defining diseases: the experience of the PISCIS Cohort. (12th September 2012) - Manzardo, C.; Esteve, A.; Ortega, N.; Podzamczer, D.; Murillas, J.; Segura, F.; Force, L.; Tural, C.; Vilaró, J.; Masabeu, A.; Garcia, I.; Guadarrama, M.; et al.
Abstract In this prospective, multicentre cohort study, we analysed specific prognostic factors and the impact of timing of highly active antiretroviral therapy (HAART) on disease progression and death among 625 human immunodeficiency virus (HIV)‐1‐infected, treatment‐naïve patients diagnosed with an AIDS‐defining disease. HAART was classified as early (<30 days) or late (30–270 days). Deferring HAART was significantly associated with faster progression to a new AIDS‐defining event/death overall (p 0.009) and in patients with Pneumocystis jiroveci pneumonia (p 0.017). In the multivariate analysis, deferring HAART was associated with a higher risk of a new AIDS‐defining event/death (p 0.002; hazard ratio 1.83; 95% CI 1.25–2.68). Other independent risk factors for poorer outcome were baseline diagnosis of AIDS‐defining lymphoma, age >35 years, and low CD4+ count (<50 cells/μL).